Current Diagnostic and Therapeutic Practices in Alopecia Areata in Two Mediterranean Countries: A Survey-Based Study - Michela Starace; Francesca Pampaloni; Elisabeth Lazaridou; Eirini Kyrmanidou; Alexander Stratigos; Aimilios Lallas; Alexander Katoulis; Dimitrios Sgouros; Federico Quadrelli; Luca Rapparini; Stephano Cedirian; Francesca Bruni; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Alopecia areata (AA) affects approximately 2% of the general population and is associated with significant psychosocial morbidity and poor health-related quality of life. Despite the high incidence of the disease the available clinical practice guidelines to help clinicians and improve patients' care are very poor and of a low methodological quality, as compared to other high-burden dermatoses. The aim of this survey is to capture the current clinical practice in AA management, as performed by dermatologists, in two Mediterranean countries to identify potential disparities and gaps in diagnosis and treatment. Methods A 50-item questionnaire was created in the English language and then translated into Greek and Italian language and sent to the Greek and Italian dermatologists via email. Results A total of 490 dermatologists from Italy and 234 from Greece participated in the survey. The diagnosis of AA is usually based on history and clinical examination, supported by trichoscopy. The rate of use of severity scores and scales to evaluate impact on quality of life by dermatologists was low. Treatment of patchy AA, in both adult and pediatric populations, is based on use of topical steroids as first-line treatment. Results on special site involvement (eyebrows, beard, and ophiasis), chronic cases, and the pediatric population highlight extreme heterogeneity in treatment approach. Conclusions Our results highlight that management of AA, in terms of diagnosis and treatment, is still challenging.